Human Herpesvirus 8 in the Prostate Glands of Men with Kaposi’s Sarcoma - Diamond, Catherine (American Society for Microbiology, 1998)
The epidemiology of human immunodeficiency virus (HIV)-associated Kaposi’s sarcoma (KS) resembles that of a sexually transmitted pathogen. However, human herpesvirus 8 (HHV-8), the proposed cause of KS, is found in semen only infrequently and at low titers. To determine whether HHV-8 was present in the urogenital tract, transrectal ultrasound-guided prostate biopsies were obtained from six men with KS (five with concurrent HIV infection) and four without KS (three with concurrent HIV) and assayed for HHV-8 by PCR. Nine of the 10 men were seropositive for HHV-8. Five of nine HHV-8-seropositive men had HHV-8 DNA detected in prostate tissue by solution-based PCR. All five currently had KS or had it previously. In two subjects, prostate tissue was the only identified source of HHV-8. In situ PCR on serial sections of prostate indicated that HHV-8 infection was localized to discrete areas of the prostate. When detected, HHV-8 DNA was present in the nuclei of >90% of the glandular epithelial cells. In situ hybridization for HHV-8 mRNA revealed that between 1 and 5% of cells harboring HHV-8 DNA expressed viral transcripts associated with HHV-8 replication (T1.1 transcript), while >90% expressed gene products associated with viral latency (T0.7 transcript). Intermittent replication of HHV-8 in the prostate and subsequent shedding of virus in semen may be crucial factors for determining whether HHV-8 can be transmitted through sexual activity.